Detection of genomic mutations in blood and urine free circulating tumour DNA in patients with inoperable and metastatic lung adenocarcinoma harbouring an EGFR mutation in tissue: a UK pilot study - Brooks, Helen; Li, Ling; Addeo, Alfredo; Stevens, Megan; Comins, Charles; Oltean, Sebastian (Frontiers in Oncology, 2023)
The development of methodologies to analyse circulating tumour DNA (ctDNA) in the blood or urine of cancer patients provides an invaluable resource that can be used for diagnosis, prognosis and to evaluate response to treatments. Lung cancer has seen in the last years a revolution in treatment strategy with the use of several classes of EGFR inhibitors. However, almost invariably, resistance to such therapies appears. In this paper we describe a pilot, longitudinal study with 20 patients with confirmed EGFR mutations on tissue biopsy for lung cancer. The objective of the study was to determine whether ctDNA from plasma and/or urine could be used to monitor the EGFR mutational status of patients with confirmed EGFR mutation positive non-small cell lung cancer (NSCLC), during treatment with an EGFR inhibitors. Blood and urine were collected monthly over periods ranging from 6-16 months. CtDNA was analysed in each patient for the presence of several known mutations that predispose to resistance to EGFR inhibitors. We have proven that serial monitoring of ctDNA from both plasma and urine is feasible, and that patients are willing to participate in this process. We have also shown that longitudinal ctDNA monitoring may detect resistance mutations before the development of radiological and clinical disease progression.